2015
DOI: 10.1111/scd.12129
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and quality of life of children and adolescents with juvenile idiopathic arthritis according to their caregivers’ perceptions

Abstract: The aim of this study was to assess the correlation between oral health indicators and oral health-related quality of life (OHRQoL) of children and adolescents with juvenile idiopathic arthritis (JIA) according to their caregivers' perceptions. Parents or guardians (mean age, 40.6 years; standard deviation [SD] = 10.97 years) of children and adolescents with JIA (n = 17; mean age, 9.8 years; SD = 2.86) and parents or guardians of healthy children and adolescents (n = 15; mean age, 10.7 years; SD = 2.16) filled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 20 publications
4
18
1
Order By: Relevance
“…Other studies reporting this effect of increased caries experience showed clearly higher values than the current study [24]. On the other hand, recent studies could not find differences in the dmf-t/DMF-T [12,13,[16][17][18][19]. It is thereby conspicuous that studies with high caries experience [24] were performed before 2000, while caries prevalence in general has been reduced during past years [33].…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Other studies reporting this effect of increased caries experience showed clearly higher values than the current study [24]. On the other hand, recent studies could not find differences in the dmf-t/DMF-T [12,13,[16][17][18][19]. It is thereby conspicuous that studies with high caries experience [24] were performed before 2000, while caries prevalence in general has been reduced during past years [33].…”
Section: Discussioncontrasting
confidence: 51%
“…The score for gingival inflammation showed an increase of one point in JIA-patients in this study compared to the general healthy population [33] (Table 4). Significantly higher presence of gingival inflammation [16,18,19] and dental plaque [12,17,19] have been reported but not by all available studies [12,13,16,18]. Reasons for the increased gingival and periodontal inflammation might be a generally increased inflammatory potential in rheumatic diseases [34] as well as affected oral behavior caused by general disease burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,7,8 In Brazilian people with SHCN, the higher prevalence of caries is associated with a negative impact. 5,8,9 Investigations in healthy children have shown that health problems such as dental caries can affect a person functionally, psychologically, and socially, in addition Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…The caries experienced did not show statistically significant differences between children with JIA and controls. 18,19 Although the pathogenesis of JIA is still not well understood, it is believed that all subtypes have autoimmune and inflammatory components. 1 Consequently, JIA is often treated with immunosuppressive agents.…”
Section: Discussionmentioning
confidence: 99%